1990
DOI: 10.1159/000235089
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Atopy and Gm Allotypes

Abstract: In 50 consecutive atopic Caucasian patients with increased IgE > 600 kU/l, the phenotypic Gm allotype constellation deviated from that to be expected, with significantly increased frequency of patients with the phenotype Gm(fnb). There was an increased frequency of the G2m(n) allotype, more frequent in patients with IgE > 1,000 kU/l, and in patients with IgG4 > 1 g/l. In patients with IgE > 1,000 kU/l, the phenotype Gm(afnb) was significantly increased and in patients with IgG4 > 1 g/l the phenotype Gm(fnb) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 14 publications
(16 reference statements)
2
16
0
Order By: Relevance
“…Finally, derangements of IgE synthesis may be a feature of some of the primary immunodeficiency disorders [32][33][34][35][36] deficiency, and conversely elevated IgE is encoun tered in patients with the DiGeorge, Nezelof, Wis kott-Aldrich and HIE syndromes. The results of our present study, taken together with the experimental and clinical studies mentioned above, suggest a close linkage between the genes for these two immunoglob ulins, and there is recent evidence for this conclusion [37,38].…”
Section: Discussionsupporting
confidence: 81%
“…Finally, derangements of IgE synthesis may be a feature of some of the primary immunodeficiency disorders [32][33][34][35][36] deficiency, and conversely elevated IgE is encoun tered in patients with the DiGeorge, Nezelof, Wis kott-Aldrich and HIE syndromes. The results of our present study, taken together with the experimental and clinical studies mentioned above, suggest a close linkage between the genes for these two immunoglob ulins, and there is recent evidence for this conclusion [37,38].…”
Section: Discussionsupporting
confidence: 81%
“…It has been shown that individuals expressing the G2m(n) and Km(l) allotypes had higher levels of antibodies to polysaccharides than those lacking these allotypes [2,6,16], In our atopic patients homo zygous of G2m(n) the highest levels of IgG2, IgG3 and IgG4 were found. Hvper-IgG4 has been reported together with increased IgE in the atopic patients with the most severe manifestations of their disease [9], It was shown recently that atopic patients with IgG4 > 1 g/1 belonged exclusively to the Gm(f,n,b) phenotype [14].…”
Section: Discussionmentioning
confidence: 99%
“…The Gm allotypes express allelic gene products, in herited in a codominant mendelian way and originat ing from epitope differences on the constant heavy chains of the IgG subclasses IgGl, IgG2 and IgG3 [7], The relationship of Gm allotypes to atopy with an increased frequency of the G2m(n) allotype and in creased frequency of patients with the phenotype Gm(f,n,b) and Gm(a,f,n,b) was recently described [14], The IgG subclass pattern of atopic patients is known to be imbalanced with increased IgG4 and oc casionally increased IgGl [9,11,18,19]. The influ ence of IgG subclass levels of Gm phenotype expres sion and gene dosage of different Gm allotypes chosen to express homozygosity and heterozygosity within each IgG subclass was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Other candidate genes investigated include, but are not limited to, the ␣ region of the T-Cell Receptor (TCR) ␣/␦ locus (Moffatt et al 1994); the ␣ 1 -Antitrypsin gene (␣ 1 -AT; Katz et al 1976;Hyde et al 1979; Liebermann and Colp 1990); histo-blood-group genetic systems (Kauffmann et al 1996); the cystic fibrosis gene (⌬F508; Mennie et al 1995;Schroeder et al 1995); Gm allotypes of IgG genes (Oxelius 1990); the Ig heavychain ␥ 4 locus (IGHG4; Amoroso et al 1996); the Clara cell-secretory-protein (CC16) locus (Laing et al 1998;Mao et al 1998); the chemokine receptor loci on chromosome 3 (Hall et al 1999;Syed et al 1999); and angiotensin-converting enzyme (ACE) gene (Benessiano et al 1997). A number of these studies have not yet been replicated in independent populations.…”
Section: Candidate Gene Approachesmentioning
confidence: 99%